Controlling the Host–Guest Interaction Mode through a Redox Stimulus. (23rd November 2017) - Szalóki, György; Croué, Vincent; Carré, Vincent; Aubriet, Frédéric; Alévêque, Olivier; Levillain, Eric; Allain, Magali; Aragó, Juan; Ortí, Enrique; Goeb, Sébastien; Sallé, Marc
Abstract: A proof‐of‐concept related to the redox‐control of the binding/releasing process in a host–guest system is achieved by designing a neutral and robust Pt‐based redox‐active metallacage involving two extended‐tetrathiafulvalene (exTTF) ligands. When neutral, the cage is able to bind a planar polyaromatic guest (coronene). Remarkably, the chemical or electrochemical oxidation of the host–guest complex leads to the reversible expulsion of the guest outside the cavity, which is assigned to a drastic change of the host–guest interaction mode, illustrating the key role of counteranions along the exchange process. The reversible process is supported by various experimental data ( 1 H NMR spectroscopy, ESI‐FTICR, and spectroelectrochemistry) as well as by in‐depth theoretical calculations performed at the density functional theory (DFT) level.